Analysis of Space Suitability Based on Marine Agriculture in The Small Islands Around Makassar - Arifin, Taslim; Bohari, Ridwan; Arlyza, Irma Shita (Universitas Muhammadiyah Surakarta, 2014)
The purpose of research is to analyze the suitability of the waters and environmental carrying capacity for utilization of marine aquaculture. Analysis of the data using conformity matrix is based on the physical-chemical parameters of the waters. Analysis of environmental carrying capacity performed to estimate the number of units that can be supported on the cultivation potential areas. The analysis is done by desk study approach, surveys and direct measurements. The analysis showed: (a) the condition of the waters of small islands around Makassar suitable for utilization of aquaculture, and (b) The water potential for seaweed cultivation around 110,012.6 ha, and the effective area about 243.225 ha. Broad potential area for grouper aquaculture by floating net system is approximately 1961.3 ha, and an effective area approximately about 209.97 ha. The results of this analysis are expected to be useful as: (1) a material consideration in the formulation of investment policy and research, (2) a reference for the public and private sectors in developing of sustainable aquaculture system effort.